(untitled) (Development Engineering Conferences Center Articles Database, 2025)
This study investigated the relationship between cognitive flexibility and social adjustment among female university students living in dormitories. The transition to university and communal living presents unique social challenges, and identifying key psychological factors that facilitate adaptation is crucial. Using a quantitative, correlational design, data were collected from 100 female residents of Imam Reza International University dormitories via the Cognitive Flexibility Inventory and a Social Adjustment Scale. Results from Pearson correlation analysis revealed a non-significant, negligible positive relationship between cognitive flexibility and social adjustment (*r* = .004, *p* = .965). Contrary to some theoretical expectations and prior research in different contexts, the findings indicate that, in this specific sample, higher cognitive flexibility was not associated with better social adjustment in the dormitory environment. The study concludes that other factors beyond general cognitive flexibility may be more critical for successful social integration in dormitory settings, suggesting that university support services should consider a multifaceted approach when designing interventions to enhance student well-being.